1997
DOI: 10.4401/ag-3825
|View full text |Cite
|
Sign up to set email alerts
|

Seismogeochemical algorithms for earthquake prediction: an overview

Abstract: While the literature abounds with case histories related to geochemical precursory phenomena, only a few studies on definite seismogeochemical algorithms have been published so far. Currently, available theoretical algorithms are based on obsolete views of fluid migration processes that do not take into account the possibility of rapid and long-distance gas migration from the focal zone. Empirical algorithms are often based on a limited number of data and need validation for several geostructural environments.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…To facilitate this analysis, a diagram depicting the correlation between Sr concentrations and 87 Sr/ 86 Sr ratios was created (see Figure 3). In this study, we observed that the 87 Sr/ 86 Sr ratio in water samples primarily ranged from 0.708 to 0.716. The occurrence of this range can be attributed to the widespread distribution of carbonates, silicates, and surface waters in the study area.…”
Section: Sr Isotopementioning
confidence: 71%
See 3 more Smart Citations
“…To facilitate this analysis, a diagram depicting the correlation between Sr concentrations and 87 Sr/ 86 Sr ratios was created (see Figure 3). In this study, we observed that the 87 Sr/ 86 Sr ratio in water samples primarily ranged from 0.708 to 0.716. The occurrence of this range can be attributed to the widespread distribution of carbonates, silicates, and surface waters in the study area.…”
Section: Sr Isotopementioning
confidence: 71%
“…By analyzing the chemical makeup of spring water (see Table 2), it was observed that Ca 2+ and Mg 2+ are widely present in the region, suggesting the presence of a significant amount of Sr. Previous research by Shand (2009) showed that 87 Sr/ 86 Sr does not participate in hydration reactions and has high mobility [54].…”
Section: Sr Isotopementioning
confidence: 98%
See 2 more Smart Citations
“…Na + , Si, and Ca 2+ concentrations and δ 2 H and δ 18 O in groundwater exhibited apparent high-value anomalies in the seismic region before and after the M 5.5 and M 5.6 earthquakes in Iceland in October 2012 and April 2013, respectively (Skelton et al, 2014). Several mechanism models have been proposed to explain the hydrogeochemical changes associated with earthquakes, such as increased solubility of rocks due to increased crustal stress and release of ions from rocks into water (Etiope et al, 1997), pore collapse due to fluid discharge (Inan et al, 2013), contact of water with exposed fresh rock surfaces, enhanced water-rock interaction (Du et al, 2010), groundwater mixing between different aquifers due to disruption of the aquifer hydraulic barrier (Wang et al, 2004), and tectonic compression leading to the uplift of deep fluids into shallow regional aquifers (Dadomo et al, 2013;Barberio et al, 2017). Among these mechanisms, the crustal strain dilation or aquifer permeability changes causing mixtures of different waters are usually considered to be the mechanism to explain these changes (Woith et al, 2013;Skelton et al, 2014).…”
Section: Introductionmentioning
confidence: 99%